Lyrik - Kojnok, Arnold (Slovakia, 2014)
An analytical film about the life, philosophy, and work of the historian Ján Mlynárik (1933 – 2012) in the context of social and political developments in the former Czechoslovakia.
Verzio Film Festival Submission
Verzio Film Festival Submission